Combining hydrophilic and hydrophobic environment sensitive dyes to detect a wide range of cellular polarity - Park, Sang Jun; Juvekar, Vinayak; Jo, Jae Hyung; Kim, Hwan Myung (Chemical Science, 2020)
Intracellular polarity is an important parameter of pathological and biological phenomena of cells; abnormal polarities are associated with diabetes, neurological diseases, and cancer. However, previously reported polarity probes have issues with quantitatively detecting intracellular polarities, can measure only a limited range of polarities, and can only detect specific intracellular regions. Here, we developed a novel two-dye system, RPS-1, that contains a new "turn-on" polarity probe (Dye1) based on a spiropyran intramolecular ring closing-opening system activated in polar protic solvents, and a benzothiadiazole containing dye (Dye3), which emits only in non-polar solvents with a large stoke shift. Individually, Dye1 and Dye3 selectively localized to lysosome and lipid droplets, respectively; however, combining these dyes, which have completely different characteristics, via a piperazine linker resulted in the staining of various intracellular organelles. Therefore, as Dye1 and Dye3 have the same absorption but different emissions, combining them resulted in a ratiometric polarity probe that could quantitatively measure a wider polarity range inside the cell using a single excitation source. In addition, ratiometric imaging using our RPS-1 probe to quantitatively detect the distribution of polarity in different cell lines indicated that lysosomes were the most polar organelles in the cell.
Keywords: Benzothiadiazoles; Biological phenomena; Hydrophilic and hydrophobic; Intracellular organelle; Neurological disease; Non-polar solvents; Ratiometric imaging; Single excitation